TEVHID-I TEDRISAT AND THE POLICY OF ISLAMIC TEACHER’S DEVELOPMENT IN TÜRKIYE (1924-1948) - Thoriquttyas, Titis (The Ministry of Religious Affairs, The Republic of Indonesia, 2024)
This study investigates the impact of the Tevhid-i Tedrisat Law on the development of religious education and teacher training in Türkiye, focusing on the law’s historical background, institutional restructuring, and influence on teacher development. Historically, Tevhid-i Tedrisat is a policy of